2000
DOI: 10.1002/1097-0223(200010)20:10<824::aid-pd926>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Normal outcome after prenatal diagnosis of thrombosis of the torcular Herophili

Abstract: We report a case of prenatal diagnosis of thrombosis of the torcular Herophili. Detection at 22 weeks' gestation by ultrasound scan of an anechoic mass located immediately above the tentorium led to magnetic resonance imaging (MRI) being performed at 28 weeks which established the diagnosis of an isolated thrombosis of the torcular Herophili. MRI remained stable throughout pregnancy, and postnatal MRI confirmed the diagnosis at 2.5 months of age. The child is now 16 months old and developing normally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Clinical data on these patients are summarized in Table 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The clinical course of live birth cases with thrombosed DSM is variable, ranging from death and neurological complications to normal neural development. However, many patients have a favorable outcome, as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on these patients are summarized in Table 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The clinical course of live birth cases with thrombosed DSM is variable, ranging from death and neurological complications to normal neural development. However, many patients have a favorable outcome, as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the torcular herophili is suspected when US scan shows a hypoechoic medial posterior ovoid mass related to the giant dural lake within an echoic mass related to the thrombus without color Doppler imaging of blood flow. 3,6,9,12,17,18 It is necessary to search on a high axial plane for an inter-hemispheric enlargement reflecting an expansion to the SSS.…”
Section: Diagnosismentioning
confidence: 99%
“…There are about 40 cases of prenatally diagnosed thrombosis of the torcular herophili in the literature (case reports [3][4][5][6][7][8][9][10] and case series [11][12][13][14][15][16] ). We present a series of eight cases, the largest single-center series yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, the prognosis of DSM seems unclear. 1,[4][5][6][7][8][9] In neonates, DSM has been associated with a poor neurological prognosis. 2,3 Conversely, Merzoug et al 6 reported 10 prenatally diagnosed cases, wherein seven cases exhibited good neurocognitive development, and concluded that the prognosis of DSM was not poor.…”
Section: Figurementioning
confidence: 99%
“…The prognosis for fetuses with this anomaly is unclear. [1][2][3][4][5] We present a case of prenatally diagnosed DSM with AV shunt and propose a new parameter for predicting a poor prognosis for fetuses with this anomaly.…”
Section: Introductionmentioning
confidence: 99%